Kepuasan Kerja Dipengaruhi oleh Kompensasi, Motivasi dan Disiplin Kerja pada Karyawan PT. Supraco Indonesia Cabang Balikpapan - Auliza Alifin Nadhiro; Syahril Hasan; Tutik Yuliani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to know the influence of Compensation, Motivation, and Work Discipline to Employee Job Satisfaction of PT Supraco Indonesia Balikpapan Branch. The type of research used is quantitative research. The sampling technique in this research is censused sampling with a population of 65 employees so the sample taken is all employees of PT Supraco Indonesia Balikpapan Branch which amounted to 65 employees. Data collection method is done by distributing questionnaires. This research uses multiple linear regression with the help of SmartPLS in processing data. The result of this research shows that compensation, motivation, and work discipline have influence on job satisfaction of PT Supraco Indonesia Balikpapan Branch employees.